Розкопки поселення доби пізньої бронзи Комишувата ХІV у 2009 р. - Горбов, В.М. (Археологічні дослідження в Україні, 2010)
In 2009, the research at Kamyshuvata XIV settlement situated on the right bank of the Kamyshuvata River, which flows into the Sea of Azov, was ongoing.